PKM Improving the Quality and Quantity of Environmentally Friendly Smoked Fish Processing in Air Dingin Village, Bukit Raya District, Pekanbaru City - Muhammad, Juandi; Gimin; Hasibuan, Saberina (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2024)
Through the Community Partnership Program (PKM), an activity can be carried out to improve the quality and quantity of smoked fish production in the MINA SALAI KUARAN business group in Air Dingin Village, Bukit Raya District, Pekanbaru, Riau to become an independent coaching group through two aspects: Increasing the level of empowerment of partners in the production aspect. Still lacking, because it uses traditional methods so that the target of this activity will result in a 50% increase in production quantity. And increasing the level of empowerment of partners in the social community aspect, this is done by using online marketing and SME information via Twitter and Facebook. Meanwhile, the lecture and discussion methods for participants are carried out directly in the field by presenting direct counseling materials that also involve students in the MBKM program, then conducting a demonstration method at the Partner's place of business. The innovation of biomass energy-based Salai fish processing technology that is made uses biomass waste raw materials from tree trunks, especially rambutan trees. The PKM activity of the MINA SALAI KUARAN business group, Making Salai Fish in Air Dingin Village, Bukit Raya District, Pekanbaru, Riau, is an application of technology with the hope of providing solutions to the obstacles faced by this MITRA, including: (1) making improvements to the management of the application of technological innovations in processing aspects of production and (2) improvements in the social aspect of society through the application of an online marketing information system and promotional media through Twitter, Facebook and MITRA's business signs, which are shown by the support and willingness to work together as partners with the community service team from the Physics Department, FMIPA, University of Riau.